Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
2 Answers
- fernando_007Lv 68 years agoFavorite Answer
integral[sqrt(x)/(x+1)] =
| first substitution y=sqrt(x) => dy=(1/2)*dx/sqrt(x) => dx=2*y*dy |
= integral[2*y^2*dy/(y^2+1)] = 2*integral[(1 - 1/(y^2+1))*dy =
= 2*y - 2*integral[dy/(y^2+1)]
| second substitution: y=tg(z) => dy=(1+tg^2(z))*dz | =
= 2*y - 2*integral[dz] = 2*y - 2*z =
= 2*[sqrt(x) - arctan(sqrt(x)]
- JJWJLv 78 years ago
Step one: Remove the sqrt term by writing down
Let y = sqrt(x). Replace sqrt(x), replace x+1 AND replace dx assuming you meant to follow the function with "dx".
That should get you started.